Risk-indicative or sustainable consumption? Consumers’ risk perception on conventional and organic food products in Poland - Mazur-Włodarczyk, Katarzyna; Wódkowska, Agata; Gruszecka-Kosowska, Agnieszka (Geology, Geophysics and Environment, 2024)
The consumption of organic food is becoming increasingly popular and, to avoid numerous threats to human health and the natural environment, the issues devoted to it require greater attention from decision-makers, producers, and consumers. Consumer decisions have an impact on shaping food consumption patterns and recently the trend of the consumption of conventional versus organic food products has been widely discussed. This is especially true given the fact that the area of human health is strongly related to the consumption of food products produced under the challenges of environmental protection and sustainability. The study aimed to investigate if the perception of consumption among Polish respondents was risk-indicative or sustainable based on the animal, fruit, and vegetable products purchased from conventional or organic production. The results revealed that fruit and vegetable consumption was not identically related with socio-demographic features, but the income level equally affected consumer choices regarding the purchase of organic food products. Gender and marital status only influenced decisions regarding the purchase of organic fruit. The consumption of animal products regarding the frequency of their consumption did not reveal the features of sustainability. The metal accumulation index (MAI) for conventionally cultivated vegetables was not higher for all of the investigated vegetables, namely pumpkin, spring onion, cabbage, lettuce, spinach, and garlic. Our study contributes to addressing the knowledge gap on consumer choices about organic food products in Poland.